Argilominerais puro e quimicamente modificados como adsorventes para corantes catiônicos - Ferreira, Maria Jackeline Duarte (2009)
The interactions between lamellar silicate with dyes have been widely studied for analytical applications that are intended as and electrochemical adsorption. In this work, sodium vermiculite (Vs) and vermiculites exchanged with copper (V/Cu) and cobalt (V/Co) and through controlled leaching (Vac1 and Vac3) were synthesized. The vermiculite reacted with nitric acid at concentrations 1.0 and 3.0 mol/dm3 originating materials named as Vac1 and Vac3. The different solids were characterized by chemical analysis, absorption spectroscopy FTIR, XRD, thermogravimetry and surface area. The solids were used as adsorbents for methylene blue dye (AM) and blue meldola (AD). Leaching of sodium vermiculite originated restructured porous solids with high surface areas whose values were 133 and 673 m2 g-1 for Vac1 and Vac3, respectively. The AM maximum dye quantities retained (Nf) were 0,042, 0,029, 0,00085, 0,020 and 0,021 mmol g-1 para os sistemas for systems Vs, Vac1, Vac3, V/Co and V/Cu respectively. For dye AD, the values of Nf were 0,038, 11.2 and 11.9 mmol g-1 for Vs, V/Cu and V/Co. It was that the adsorption capacity was independent of the nature of the dyes, but was influenced by the interlayer cation. The interactive processes dye/clay reactions involving the insertion and/or ion exchange. Regardless of the solid, it was observed that as the leaching became more pronounced, was deacreased companing with the original vermiculite the reactivity of the activated matrices for the original vermiculite. Solids derived from vermiculite have shown potential adsorbents for species pollutants such as organic dyes in solution.